2017
DOI: 10.1056/nejmoa1414216
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Vesicular Stomatitis Virus Ebola Vaccine

Abstract: Background The worst Ebola virus disease (EVD) outbreak in history has resulted in more than 28,000 cases and 11,000 deaths. We present the final results of two phase 1 trials of an attenuated, replication-competent, recombinant vesicular stomatitis virus (rVSV)–based vaccine candidate designed to prevent EVD. Methods We conducted two phase 1, placebo-controlled, double-blind, dose-escalation trials of an rVSV-based vaccine candidate expressing the glycoprotein of a Zaire strain of Ebola virus (ZEBOV). A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
303
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(322 citation statements)
references
References 25 publications
9
303
2
8
Order By: Relevance
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Vaccines that were assessed in phase I and/or II studies during the 2013-2016 EBOV epidemic include rVSV-EBOV [268][269][270][271][272] , Ad5-EBOV [273][274][275] , rVSV-EBOV combined with rAd5-EBOV 276 , ChAd3-EBOV with or without MVA-EBOV [277][278][279][280] , Ad26-EBOV combined with MVA-EBOV 281 , and DNA encoding multiple filovirus GPs 282,283 . These EBOV vaccines generally elicited good immunogenicity against EBOV GP, and no serious adverse events were described.…”
Section: Vaccination Of Humansmentioning
confidence: 99%
“…Early results on humoral and cell-mediated responses of ChAd3-EBOV were promising overall, although somewhat mixed (12,13), and similarly encouraging humoral responses to rVSV-ZEBOV were found at day 28 after vaccination (14). These small studies of both vaccines had not detected any safety issues, but in midDecember 2014, a phase I study under way in Switzerland that used rVSV-ZEBOV was paused to assess episodes of reported arthritis that began during the second week after vaccination.…”
Section: Vaccine Selectionmentioning
confidence: 99%
“…In early January 2015, the study was resumed at a lower dose of vaccine (15). Investigators of other phase I studies in the United States examined their data but did not initially detect similar adverse events (14), although an association was detected later in some other trials also.…”
Section: Vaccine Selectionmentioning
confidence: 99%
“…Currently trial success was exhibited with the VSV-ZEBOV recombinant, live attenuated, replicationcompetent genetically engineered vesicular stomatitis virus vaccine (Regules et al, 2015;Henao-Restrepo et Kashangura 55 al., 2017). The vaccine candidate (rVSV-ZEBOV) is genetically engineered to replace the VSV glycoprotein with the glycoprotein from a Zaire strain of Ebola virus (ZEBOV) (Regules et al, 2015).…”
Section: Potential Development Of Anti-ebov Line 1 (Designed Gp Sequementioning
confidence: 99%